Дослідження засобів безпеки в системах електронної комерції - Карабанов, Д. С.; Чеботарьова, Д. В. (ХНУРЕ, 2024)
The work is devoted to the research of current problems of information security and the analysis of modern security tools in electronic commerce systems. Recently, the number of cyber-attacks and fraud in e-commerce systems has increased significantly. A comprehensive approach to solving information security problems, including the use of modern software and technical tools, improvement of regulatory and legal support, implementation of certain organizational measures, will allow to achieve effective results in the field of protection of electronic commerce systems.
Keywords: електронна комерція; electronic commerce